An update to depression case management by practice nurses in primary care: a service evaluation. Issue 9 (27th March 2014) - Murphy, R.; Ekers, D.; Webster, L.
<x xml:space="preserve">Abstract</x> Accessible summary There is a recognized need to enhance non‐pharmaceutical interventions in a way that is more accessible to the primary care population. Collaborative care has been shown to have a positive impact upon depression symptoms and a core element of the collaborative care approach is the case manager. This paper is a service evaluation of a collaborative care intervention that uses primary care nurses as the depression case manager and is a follow‐up to the service audit carried out by Ekers and Wilson. The results support the notion that primary care nurses are ideally placed for delivering care to depressed patients; especially in cases were a patient also has a comorbid long‐term medical condition. Abstract There is a recognized need to enhance non‐pharmaceutical interventions for depression in the primary care. This service evaluation of collaborative care for depression by primary care practice nurses is an update of Ekers and Wilson (2008), reporting outcomes 5 years following initial training. From an initial 13 trained practice nurses, three provided anonymized data. Mean post‐treatment Patient Health Questionnaire‐9 (PHQ9) score was 8 [standard deviation (SD) 6.53, n = 185], indicating a mean positive change in depression symptom level of 8.9 [SD 7.01, 95% confidence interval (CI) 7.89–9.93, P < 0.001]. Subgroup analysis for patients identified with a comorbid long‐term conditions (LTC) mean post‐treatment PHQ9 score was 9 (SD 7.72, n = 33), indicating a mean positive change in depression symptom level of 8.1 (SD 5.79, 95% CI 6.04–10.41, P < 0.001). Nurses provided feedback on the intervention showing potential areas that would benefit from further detailed qualitative review. It was concluded that primary care practice nurses would be ideally placed to deliver collaborative care to depression patients with comorbid LTCs.